How Does Psychological Capital Buffer Job Stress in Dental Healthcare Workers? - Desi Andriyani; Lies Elina Prasetiowati (Inovasi Analisis Data, 2025)
Objective: The influence of organisational factors and psychological resources on occupational well-being in dental healthcare is examined in this study. It looks at how work engagement, safety climate and transformational leadership directly impact job burnout, and whether psychological capital strengthens these protective factors. Methods: To measure the key concepts, we used scales that had been shown to be valid. Information was examined via structural equation modelling and hierarchical regression to evaluate direct and moderating impacts, with measurement models confirmed for reliability and validity. Findings: The analysis shows that work engagement, safety climate and transformational leadership can all play a key role in preventing job burnout. Also, good mental health can make these bad relationships much better. Individuals with high levels of psychological capital demonstrate a greater ability to convert supportive work conditions into sustained well-being. Novelty: This research is pioneering because it shows how organisational resources and personal capabilities work together. Psychological capital is established not just as a complementary factor, but as a catalytic resource that optimises the impact of workplace conditions on professional health. Research Implications: The study provides a theoretical advancement by integrating organisational and positive psychology perspectives. Psychological capital is identified as a strategic leverage point for the purpose of practice. This suggests that interventions targeting this resource can maximise the effectiveness of organisational support systems. The result of this is that sustainable professional practice and enhanced care quality are promoted.